Thomas Reid's theory of perception - Nichols, Ryan.; Oxford eBooks (Oxford : Clarendon, 2007)
Offering an interpretation of the 18th century Scottish philosopher Thomas Reid's theory of perception, this work develops Reid's unheralded argument against a representational theory of thought, which the author applies to his discussion of the intentionality of perceptual states and Reid's appeal to 'signs'.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Reid, Thomas, -- 1710-1796.; Perception (Philosophy); Electronic books